Burhaana Rabbih and Self-Control: A Model of Sustainable Resistance to the Digital Moral Crisis - Muhammad Sulaiman Nuh; Rahmat Hidayat; Sulaiman Mohammad Nur (al-Afkar, Journal For Islamic Studies, 2026)
The development of digital technology has given rise to increasingly complex moral challenges, marked by increased impulsive behavior, weakened self-control, and the normalization of deviance through social media. This phenomenon demonstrates that conventional normative and psychological approaches have not been fully able to address the recurring and ongoing moral crisis. This article aims to examine the meaning of Burhāna Rabbih in Surah Yusuf verse 24 and integrate it with Baumeister's self-control theory to formulate a sustainable resistance model as a framework for moral resilience in the digital era. This research uses a qualitative approach with library and thematic interpretation (maudhu'i) methods, as well as an interdisciplinary analysis of Qur'anic studies and modern psychology. Data were obtained from the Qur'an, classical and contemporary commentaries, psychological literature from the past five years, and empirical reports related to digital moral phenomena. The results show that Burhāna Rabbih functions as a spiritual-psychological mechanism that strengthens moral standards, internal motivation, self-awareness, and volitional strength. The integration of this concept with Baumeister's self-control theory produces a sustainable resistance model that can explain moral resilience in a sustainable manner, not just situationally. This research contributes to the development of interdisciplinary thematic interpretations and offers an alternative approach to strengthening morals and self-control in the digital era.